8 The effect of BTK inhibitors on platelet aggregation in acute coronary syndromes. (June 2018) - Bhatti, Maria; Ayton, Sarah; Michail, Olga; Gollop, Nicholas D; Ryding, Alisdair; Rushworth, Stuart; Bowles, Kristian; Flather, Marcus
Abstract : Introduction: Dual antiplatelet therapy is a cornerstone of long term management of Acute Coronary Syndrome (ACS), but despite this there is a residual risk of morbidity and mortality. Bruton's Tyrosine Kinase (BTK) inhibitors are currently indicated for management of certain haematological malignancies, but have additionally been found to inhibit platelet aggregation through the Glycoprotein VI (GPVI) collagen mediated pathway. This study evaluates the effects of BTK inhibitor on platelet aggregation after ACS. Methods: Patients with a confirmed diagnosis of ACS were enrolled and blood samples obtained within 48 hours of hospital admission. All patients had been initiated on dual antiplatelet therapy; aspirin plus a P2Y12 inhibitor (clopidogrel or ticagrelor). Blood samples were treated ex vivo with increasing concentrations of Ibrutinib (0, 0.5, 1, 2 mmol/litre). Platelet aggregation was measured in response to collagen using a Multiplate analyser to estimate the area under the curve (AUC), with lower AUC values indicating lower platelet aggregation. Results: Twenty participants had blood samples treated with increasing concentrations of Ibrutinib. The median age was 63 years and 80% were male. The median AUC values for Ibrutinib concentrations 0 (control), 0.5, 1 and 2 mmol/L were 18.5, 8 (p=0.0004), 4.5 (p<0.0001) and 2 (p<0.0001) units, respectively indicating significant inhibition of platelet aggregation (figure 1). Conclusion: The BTK inhibitor Ibrutinib provides further inhibition of platelet aggregation in ACS patients receiving dual antiplatelet therapy in a dose dependent manner. These results provide a rationale for BTK inhibitors to be tested as a potential new antiplatelet therapy for ACS.